The Association of A Number of Risk Factors With Depression in Patients With Prostate Cancer Undergoing Androgen Deprivation Therapy - Kim, Chang Hee; Kim, Kwang Teack; Oh, Jin Kyu; Chung, Kyung Jin; Kim, Tae Beom; Jung, Han; Yoon, Sang Jin; Kim, Khae Hawn (Urology Journal, 2018)
Purpose: To identify factors affecting depressive symptoms in patients undergoing androgen-deprivation therapy (ADT) to treat prostate cancer. Materials and Methods: The patients with prostate cancer visiting the psychiatry department without referral because of depressive symptoms while undergoing ADT participated. To assess depressive symptoms, the Beck Depression Inventory (BDI) was used. To identify the risk factors affecting depressive symptoms, univariate regression and multiple linear regression analyses were implemented. Results: The mean (± SD) age, age when initiating ADT, duration of ADT, serum testosterone level and BDI scores of participants (n = 45) were 73.9 ± 7.9 years, 72 ± 8.5 years, 33 ± 31.6 months, 214.9 ± 219.5 ng/dL and 18 ± 13.5 points. The androgen dependent and independent were 26 and 9 patients. Eight of these androgen-independent patients underwent concurrent chemotherapy. Twenty-one patients were treated with bicalutamide and 24 with leuprolide. Of the clinical variables affecting BDI scores, the type of ADT drug (P < 0.001), serum testosterone level (P = 0.003), and age at diagnosis (P < 0.001) were significant. Conclusion: Efforts to diagnose and treat depression appropriately, especially if depressive symptoms change in patients undergoing ADT to treat prostate cancer who are using an LHRH agonist (leuprolide), have low testosterone level, or are older at the age when initiating ADT.